2022
DOI: 10.1007/s10461-022-03768-5
|View full text |Cite|
|
Sign up to set email alerts
|

Do Couple-Based Interventions Show Larger Effects in Promoting HIV Preventive Behaviors than Individualized Interventions in Couples? A Systematic Review and Meta-analysis of 11 Randomized Controlled Trials

Abstract: This systematic review and meta-analysis aims to compare the effects of couple-based prevention interventions against individual-level interventions on HIV prevention in randomized controlled trials (RCTs), identify potential moderators, and assess study quality. Eleven RCTs were included, comprising 3933 couples in the intervention group and 7125 individuals in the individual control group, predominantly in heterosexual couples from the USA and Africa. Couple-based interventions had a more significant effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“…For example, Crepaz and colleagues [ 6 ] showed in a meta-analysis that CBIs (as opposed to individual interventions) resulted in increased odds (odds ratios between 1.51 to 1.79) of HIV testing, condom use, and nevirapine uptake to reduce mother to child transmission of HIV. Similar findings have been shown by other researchers [ 7 , 8 ], including studies conducted in South Africa [ 9 , 10 ]. To date, however, only two studies in the USA have tested the use of a CBI to improve ART adherence, and both found it to be superior to usual care in serodiscordant couples [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…For example, Crepaz and colleagues [ 6 ] showed in a meta-analysis that CBIs (as opposed to individual interventions) resulted in increased odds (odds ratios between 1.51 to 1.79) of HIV testing, condom use, and nevirapine uptake to reduce mother to child transmission of HIV. Similar findings have been shown by other researchers [ 7 , 8 ], including studies conducted in South Africa [ 9 , 10 ]. To date, however, only two studies in the USA have tested the use of a CBI to improve ART adherence, and both found it to be superior to usual care in serodiscordant couples [ 11 , 12 ].…”
Section: Introductionsupporting
confidence: 92%
“…CBIs offer an advantageous approach over individual-based interventions in improving several HIV-related outcomes [6][7][8][9][10]. Our ultimate goal is to add to this body of knowledge by examining the effect of a CBI targeting women's ART adherence in KwaZulu-Natal.…”
Section: Discussionmentioning
confidence: 99%
“…Provision of information and counseling messages continue to be important; we found evidence that couples counseling and motivation-oriented counseling approaches are effective. Couples counseling is effective and widespread in many contexts [ 139 ]; motivation-oriented counseling is less broadly scaled and may merit further expansion; economic empowerment interventions may have broad reaching effects beyond HTS [ 140 ]. However, individualized messaging—both personalized messages and personal invitation letters—had minimal impact on uptake of HTS and may be considered for de-prioritization.…”
Section: Discussionmentioning
confidence: 99%